IMPLEMENTASI KEBIJAKAN HUKUM SERTIFIKASI HALAL PADA USAHA KECIL DAN MENENGAH DI INDONESIA - Rukman, Auliah Andika; Suhra, Andi Amalia; Elviana, Elviana (Restorative Journal, 2024)
ABSTRACT                  This research will examine the implementation of halal certification legal policies for Micro and Small Business actors in Indonesia. Currently, to be able to compete in the national market and global market, the need for halal guarantees for Micro and Small Business products is very much needed, especially in Indonesia, which is a Muslim-majority country, of course. Product standards must be based on Islamic law, the law also requires that all products located in the territory of the Unitary State of the Republic of Indonesia must obtain a halal certificate. This research uses a normative juridical method with a descriptive approach to analyze various literature, regulations and government policies related to Halal Certification for micro and small businesses. The research results show that with clear regulations and mechanisms in place, it is hoped that the implementation of this halal certification policy can provide legal certainty, security and comfort for consumers in using halal products, as well as encourage improvements in product quality and halalness for business actors, including micro and small businesses.